Library associations in the Philippines, 1993-1998 analysis of training programs - Correo, Lorella P. (2000)
Seminars and conferences are conducted by library associations every now and then. This study was done to find out what training programs were conducted by the nine library associations in the Philippines, namely: ALAP; ASLP; MAHLAP; PAARL; PASL; PATLS; PGLL; PLAI; and PLAP. It aimed to determine what topics were covered in the different seminars and conferences by what associations, which of the topics had the most/least number of training programs, and what factors the associations considered in preparing for seminars and conferences. This covered the years from 1993 to 1998, a six year period.